Does climate-smart agriculture make economic sense to farmers? Yes, and there's more evidence than you think - Nowak, Andreea C.; Rosenstock, Todd S.; Namoi, Nictor; Lamanna, Christine; Steward, Peter R. (2019)
Initial and sustained use of Climate-Smart Agriculture (CSA) often hinges on the economic costs, benefits and risks of the new management practice, as well as farmer’s socio-economic endowments. However, data showing the economic performance of CSA is rarely presented. Incomplete or missing information limits the interest of investors at all levels—donors, governments, private sector, and farmers.Initial and sustained use of Climate-Smart Agriculture (CSA) often hinges on the economic costs, benefits and risks of the new management practice, as well as farmer’s socio-economic endowments. However, data showing the economic performance of CSA is rarely presented. Incomplete or missing information limits the interest of investors at all levels—donors, governments, private sector, and farmers.